Building Poklahsar Capacity to Increase Sales Through Digital Marketing Strategies in Kendalbulur Village - Rico Andhika Putra; Ayu Nofitasari; Yelma Dianastiti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
Expanding markets for Micro, Small, and Medium Enterprises is crucial for increasing product sales. One of the main challenges these enterprises face is limited marketing reach. Based on preliminary observations and discussions with Poklahsar groups in Kendalbulur Village, specifically Poklahsar Mina Sumber Pangan and Poklahsar Patin Condong Raos, which produce processed catfish-based products, training in digital marketing strategies was needed. To improve product competitiveness and broaden market reach to the national level, digital marketing represents a highly promising approach. This study aimed to deliver training for Poklahsar on the role of digital marketing in expanding market reach and strengthening promotional activities. The training used lectures and hands on practice, with Instagram as the primary digital marketing platform. It included educational sessions on digital marketing and step by step tutorials on how to create and manage Instagram accounts effectively. The training is able to strengthen the capacity of these Micro, Small, and Medium Enterprises, support business development, expand market access, and enhance product competitiveness.